2000
DOI: 10.1016/s0895-7061(99)00165-x
|View full text |Cite
|
Sign up to set email alerts
|

Candesartan cilexetil is not associated with cough in hypertensive patients with enalapril-induced cough

Abstract: The aim of this study was to evaluate the occurrence of dry cough during treatment with candesartan cilexetil, enalapril, or placebo in patients with hypertension and a history of angiotensin converting enzyme (ACE)-inhibitor-related cough. Patients with confirmed cough during an enalapril (10 mg) challenge period, followed by no cough during a placebo dechallenge period were randomized to 8 weeks of double-blind treatment with candesartan cilexetil (8 mg) (n = 62), enalapril (10 mg) (n = 66), or placebo (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…Using routinely collected primary care data, we are able to demonstrate that the 1, 2–3, and 4–6 month discontinuation rates for ramipril, simvastatin, and ARBs are similar to previously published ADR rates obtained from large clinical trials and postmarketing studies 20 32 …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Using routinely collected primary care data, we are able to demonstrate that the 1, 2–3, and 4–6 month discontinuation rates for ramipril, simvastatin, and ARBs are similar to previously published ADR rates obtained from large clinical trials and postmarketing studies 20 32 …”
Section: Discussionsupporting
confidence: 75%
“…Using routinely collected primary care data, we are able to demonstrate that the 1, 2-3, and 4-6 month discontinuation rates for ramipril, simvastatin, and ARBs are similar to previously published ADR rates obtained from large clinical trials and postmarketing studies. [20][21][22][23][24][25][26][27][28][29][30][31][32] We identified that approximately 10% of patients prescribed ramipril discontinued within 31 days of their first prescription, a figure similar to previously published data, suggesting that between 13% and 18% of patients prescribed ramipril suffer an ADR and 8% discontinue treatment within 8 weeks of starting. [20][21][22] Similarly for simvastatin, 13.0% of patients discontinued within 3 months and 16% within 6 months of starting, figures similar to previous reports suggesting that 16% to 18% of patients prescribed simvastatin suffer an adverse drug event (ADE) and 18% discontinue therapy over a 3-to 6-month period.…”
Section: Comparison With Other Studiessupporting
confidence: 79%
“…Contraindications to treatment were considered rare because most individuals not tolerating an ACE can receive an ARB with a low likelihood of side effects. 29,30…”
Section: Use Of Ace/arb Therapymentioning
confidence: 99%
“…Cough was infrequent in comparison with placebo (1.6% with candesartan vs. 1.1% with placebo) (8). In a placebo-controlled trial of 154 patients with a confirmed history of ACEI-induced cough, treatment with candesartan cilexetil, 8 mg/day over 8 weeks, significantly lowered the frequency and severity of dry cough to a level not significantly different from that reported in placebo recipients (97). This finding has been confirmed in a comparative trial of enalapril and calcium antagonists.…”
Section: Adverse Drug Reactions and Tolerabilitymentioning
confidence: 64%
“…In hypertensive patients with confirmed enalapril-induced cough, the incidence (35.5% vs. 68.2%) frequency and severity of dry cough was significantly lower with candesartan cilexetil than with enalapril and not different from that found with placebo (97).…”
Section: Clinical Studies Hypertensionmentioning
confidence: 66%